Metastatic Prostate Cancer Synchronous with Male Breast Papillary Ductal Carcinoma in situ: Management Dilemma and Literature Review - Hasbullah, Harissa Husainy (Case Rep Oncol, 2021)
Prostate cancer is common in men, but tumour of the male breast is rare. For these two tumours to be presented synchronously in a male patient is even rarer. The focus of this paper is the case of a 72-year-old man diagnosed with papillary ductal carcinoma in situ after he presented with a unilateral breast mass associated with nipple discharge. Imaging staging for his breast tumour and subsequent prostate biopsy found an incidental synchronous asymptomatic prostate adenocarcinoma as well as bone metastases. He denies risk factors for malignancies and refuses genetic testing. The first part of our discussion will highlight the uncommon occurrence of male breast ductal carcinoma in situ and its management controversies. The subsequent part of our discussion will focus on the association between male breast cancer and prostate cancer, and implication of this on the future treatment of these patients. More importantly, our case will illustrate the challenges in managing dual primaries that present concurrently.